Aplikasi Exmath: Bagaimana Respon Peserta Didik? - Arifah, Marisa Devi Isnaini; Rahmawati, Dewi; Anggraini, Seftika; Prabowo, Anggit (Mandalika Mathematics and Educations Journal, 2023)
Technological advances have an impact on all sectors of human life, one of them is the education sector. This sector has an important role in realizing the progress of the nation. The use of Information and Communication Technology (ICT)-based learning media in the classroom is one of the right interventions in the use of ICT in education. The purpose of this study is to find out the response of students after using learning media in the form of the EXMATH application. This media was developed by combining Microsoft Power Point and i-Spring Suite software. The subject matter contained in the media is exponential and logarithmic material. The respondents in this study consisted of 16 students of class X at SMA Negeri 1 Ngemplak, Sleman. They were given a questionnaire consisting of six statement items. Each statement uses a Likert scale of five. The data analysis used in this study is descriptive statistics using qualitative methods. The results of this study indicate that after students use the EXMATH application, students feel the positive impact of the application. Some of the positive impacts felt by students were that students felt happy, learning was not boring, and interest in learning increased. In addition, students also get new experiences when learning mathematics with applications.